PHYSALIS ANGULATA O‘SIMLIGI VITAMIN TARKIBI TAXLILI - Xikmatullayev , Izzatullo (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
For the first time, the HPLC method was used to determine the content of water-soluble vitamins in the plant Physalis angulata of the Solanaceae family, growing in Uzbekistan.